Advances in the quality of the Malaysian environment - the role of environmental education. - Muhammad, Badri; Yaziz, Mohd. Ismail; Awang, Muhamad (1988)
There is concensus among world leaders for the adoption of the principle of environmentally sound and sustainable development in the quest for environmental quality preservation. There is also agreement that policies which follow from the need for sustainable development must include,amongst others,preserving peace,reviving economic growth,remedying the problems of poverty,merging environment and economics in decision making,etc. and governments are encouraged to integrate environmental considerations in their planning and development policies and programmes. This can be accomplished more easily if policy makers themselves are knowledgeable about the environment and if their actions are backed by environmentally concious citizens. The Malaysian non-tertiary education system is making a conciuos effort to integrate environmental awareness and responsibility among students in schools. At the tertiary level,courses with existing environmental components are availabe for students in common existing disciplines e.g. engineering,medicine,and a full integrated professional programmes leading to a degree in Environmental Science is also offered. Non-formal,environmental education is less well organized and is largely dependent upon the activities of the mass media and the NGOs. Nonetheless,the trend indicates development of closer rappour between NGOs and government agencies and this is expected to further enhance non-formal EE activities for the benefit of the public and also the country at large.